2018
DOI: 10.1039/c8fd90005a
|View full text |Cite
|
Sign up to set email alerts
|

Photocrosslinking between nucleic acids and proteins: general discussion

Abstract: Dimitra Markovitsi replied: Your papers have indeed been very stimulating for our studies. However, in our experiments, using much lower excitation intensities (<4 mW cm À2) than yours (>4 mW cm À2), we found that the one-photon ionization of mono-nucleosides and mono-nucleotides is lower than 3 Â 10 À4 , which corresponds to our detection limit. In contrast, when using similar excitation intensities to those reported in your 2002 paper we do observe ionization from the buffer. The fact that we observe one-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Other researchers have noted in passing the increased presence of aromatic amino acid side chains in UV cross-linking data sets (see refs 18,19,33,48,61 ), but have not to our knowledge recognized its role as a trigger for cross-linking, nor distinguished between direct and indirect cross-link events. It is clear that additional factors may also contribute to cross-linking events in RNA-protein sites, including: efficiency of the photo-induced electron transfer, the ability to stabilize free radicals, the flexibility of the system to adopt to the configurations that are required for the radical reactions 62 and the proximity of reactive pairs 63 (Sarnowski et al; in preparation). Furthermore, our findings cannot explain all RNA-protein cross-linking reactions, at least those involving sulphurcontaining amino acids, such as cysteine, which are highly photoreactive and prone to cross-link probably due to the high reactivity of the thiyl radical 19,34,55 .…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have noted in passing the increased presence of aromatic amino acid side chains in UV cross-linking data sets (see refs 18,19,33,48,61 ), but have not to our knowledge recognized its role as a trigger for cross-linking, nor distinguished between direct and indirect cross-link events. It is clear that additional factors may also contribute to cross-linking events in RNA-protein sites, including: efficiency of the photo-induced electron transfer, the ability to stabilize free radicals, the flexibility of the system to adopt to the configurations that are required for the radical reactions 62 and the proximity of reactive pairs 63 (Sarnowski et al; in preparation). Furthermore, our findings cannot explain all RNA-protein cross-linking reactions, at least those involving sulphurcontaining amino acids, such as cysteine, which are highly photoreactive and prone to cross-link probably due to the high reactivity of the thiyl radical 19,34,55 .…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have noted in passing the increased presence of aromatic amino acid side chains in UV cross-linking data sets (see refs 18,19,33,48,61 ), but have not to our knowledge recognized its role as a trigger for cross-linking, nor distinguished between direct and indirect cross-link events. It is clear that additional factors may also contribute to cross-linking events in RNA-protein sites, including: efficiency of the photo-induced electron transfer, the ability to stabilize free radicals, the flexibility of the system to adopt to the configurations that are required for the radical reactions 62 and the proximity of reactive pairs 63 (Sarnowski et al; in preparation). Furthermore, our findings cannot explain all RNA-protein cross-linking reactions, at least those involving sulphurcontaining amino acids, such as cysteine, which are highly photoreactive and prone to cross-link probably due to the high reactivity of the thiyl radical 19,34,55 .…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies, it was found that G -quadruplexes exhibit a larger propensity than duplexes to photoeject an electron upon absorption of low energy photons. One hypothesis suggested previously is that electron ejection occurs after population of excited charge transfer states involving different bases, followed by charge separation [74]. According to such a scenario, the guanine core should behave as a deep trap for the positive charge, the negative charge remaining on an external base (adenine or thymine).…”
Section: Discussionmentioning
confidence: 99%